SUBCRONIC TOXICITY TEST OF EXTRACT PERIA FRUIT (Momordica charantia L) ON WISTAR RATS TOTAL CHOLESTEROL (UJI TOKSISITAS SUBKRONIK EKSTRAK PERIA (Momordica charantia L) TERHADAP KADAR KOLESTEROL TOTAL TIKUS WISTAR) - Welly Ratwita; Fransiska Ambarukmi; Anieq lyatunafsy Syifa (Fakultas Kedokteran Gigi Unjani, 2022)
Bitter melon had been widely used by the community as traditional medicine and proven to have effects including antidiabetic, anti-inflammatory, antipyretic, antioxidant, antitumor. Further testing is needed to determine the toxic effects that have not been detected in the acute toxicity test, the subchronic toxicity test. This study aims to assess the toxicity seen from the number of deaths, changes in body weight, changes in the weight of rat liver, and cholesterol levels in rat blood. This research is an experimental study using the Posttest Only Control Group Design method. A total of 40 male and female rats wistar strains were divided into a control group (K) and 3 treatment groups (P). Each group consisted of 5 male rats and 5 female rats. Group K is only given food (pellets) and drinking water. P1, P2, and P3 groups were given feed (pellets), drinking water and ethanol extract of peria fruit (Momordica charantia L.) at levels of 250 mg/kg, 500 mg/kg, and 1000 mg/kg. After the first 24 hours of administration the number of rats that died was counted, the change in body weight was weighed for 29 days and on the 29th day a rat’s blood was taken to calculate the cholesterol level of the rat, surgery was also performed to weigh the relative organ weigh of the rat liver. There were no rat deaths in the entire group, there were no weight loss, relative liver organ weight, and cholesterol levels were significant in all group(p>0,05). The ethanol extract of peria fruits in this study showed no toxic. The dose has reached the maximum dose of 1.000 mg/kg but the results have no effect on death, body weight, relative organ weight of the liver, and cholesterol levels. DOI : 10.54052/jhds.v1n3.p233-246